Konsep dan Teori Kurikulum dalam Dunia Pendidikan - Ahid, Nur (Program Pascasarjana UIN Sunan Ampel Surabaya, 2006)
The concept of curriculum develops along side with the development ofeducation. It is also varied according to schools of thought and the theories it upholds.The value of curriculum cannot be looked at only from the written document. It mustalso be judged from its implementation in the classes. Curriculum is not merely a writtenteaching plan. It is also a function that operates in the classes, a guideline and regulationsfor both the milieu and activities in these classes. For this reason, curriculum can beunderstood as a set of regulations that a student must undergo in order to achievecertain degree or certificate. In the meantime, theory is a set of statements that areorderly structured in a way that give functional meaning to a series of events. The theoryof curriculum includes: the concept of curriculum, its assignment, development, design,implementation and evaluation. There are three concepts however in relation to curriculum,namely (1) curriculum as a substance, (2) curriculum as a system, and (3) curriculum asa field of study. Concerning the later, curriculum has become the subject of study by theexperts in the field of education and teaching. The aim of curriculum as a field of studyis to develop a science of curriculum and its system.